A Proposed Measurement Instruments for Total Quality Management Practices in Higher Education Institutions - Kamarul Bahari Yaakub (Tanjong Malim, 2019)
A Proposed Measurement Instruments for Total Quality Management Practices in Higher Education Institutions by Kamarul Bahari Yaakub